2012
DOI: 10.1055/s-0032-1316454
|View full text |Cite
|
Sign up to set email alerts
|

Silent kills

Abstract: Zusammenfassung Wenn Pflegekr?fte bemerken, dass bei der Behandlung eines Patienten etwas nicht stimmt, und sie trotzdem nichts sagen, kann dieses Schweigen t?dliche Konsequenzen f?r den Patienten haben. Im zweiten Teil der US-amerikanischen Studie erfahren Sie, welche M?glichkeiten Pflegekr?fte haben, sich Geh?r zu verschaffen, und welche Ma?nahmen auf organisatorischer Seite getroffen werden k?nnen, um die Kommunikation auf Intensivstationen zu verbessern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Many studies document their reluctance to verbally intervene when they witness a colleague ignoring established safety protocols (Maxfield et al . ), selecting the wrong therapy (Blatt et al . ), or neglecting to recognise or act upon a dangerous change in a patient's condition (Lyndon , Simpson and Lyndon ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies document their reluctance to verbally intervene when they witness a colleague ignoring established safety protocols (Maxfield et al . ), selecting the wrong therapy (Blatt et al . ), or neglecting to recognise or act upon a dangerous change in a patient's condition (Lyndon , Simpson and Lyndon ).…”
Section: Introductionmentioning
confidence: 99%
“…The American Association of Critical Care Nurses conducted a survey of critical care healthcare providers, among them 1,143 nurses. While the purpose of this study was not to investigate bullying per se, the researchers found that 88% reported working with team members who divide the team, often at another's expense; 77% claimed that they worked with someone who is disrespectful, of which 33% were verbally abusive; and 52% reported that they worked with people who abused their authority, including pulling rank and bullying (Maxfield, Grenny, McMillan, Patterson, & Switzler, ). A study of 206 Turkish nurses (Efe & Ayaz, ) found that intensive care unit (ICU) nurses were more exposed to “mobbing” behaviors compared to other nurses.…”
mentioning
confidence: 99%
“…VitalSmarts conducted a further study in 2010 “The Silent Treatment” and showed that a culture of silence in organizations leads to communication breakdowns that harm patients. 3 This study found that more than four out of five nurses have concerns about dangerous shortcuts, incompetence, or disrespect. More than half say shortcuts have led to near misses or harm; more than a third say incompetence has led to near misses or harm; and more than half say disrespect has prevented them from getting others to listen to or respect their professional opinion.…”
Section: Introductionmentioning
confidence: 74%